Forensic and population genetic analysis of Serbian population using 21 STR loci of GlobalFiler™ PCR amplification kit. Issue 1 (December 2019) - Zgonjanin, Dragana; Almheiri, Reem; Alghafri, Rashed; Nedić, Dalibor; Stojiljković, Goran
Abstract: Autosomal short tandem repeats (STRs) have been widely used in forensic investigations. Prior to the application of any DNA based identification method, it is essential to estimate the allele frequencies and forensic statistical parameters of targeted STR loci in each population in order to provide a more precise reference database for forensic investigation. The GlobalFiler™ Kit is a multiplex assay that combines the 13 original CODIS loci with 7 non-overlapping loci from the expanded European Standard Set (ESS), as well as the highly discriminating SE33 locus, two Y-based loci and the sex determining maker, Amelogenin. The full complement of loci in the GlobalFiler™ Kit are: D13S317, D7S820, D5S818, CSF1PO, D1S1656, D12S391, D2S441, D10S1248, D18S51, FGA, D21S11, D8S1179, vWA, D16S539, TH01, D3S1358, AMEL, D2S1338, D19S433, DYS391, TPOX, D22S1045, SE33 and a Y-specific insertion/deletion locus (Yindel). The 6-dye GlobalFiler™ PCR Amplification kit (ThermoFisher Scientific) comprises 21 autosomal STRs have already been proven to be able to provide reliable DNA profiling results and enhance the power of discrimination between individuals. In this study, we are presenting an analysis of GlobalFiler STR loci on 209 unrelated individuals from Serbia.